Դիվանագիտական բանակցությունները Բաթումում. Անդրկովկասյան պետության կազմալուծումը. Երեք անկախ պետությունների ստեղծումը (1918 թ. մայիս) - Պետրոսյան Գեղամ (YSU Journal of International Affairs, 2017)
The article deals with the issues of diplomatic negotiations in Batumi and the dismantling of the Transcaucasian state, as well as the creation of three independent republics. In Batumi, it became clear that the Turkish side abandoned its previous position on negotiating on the basis of the Treaty of Brest-Litovsk and put forward new, more serious territorial demands for the whole of the Caucasus and Armenia in particular. Through Transcaucasia, Turkey sought to pave the way for the Turkic-speaking regions of Central Asia. Such aspirations of Turkey contradicted the geopolitical and economic interests in the South Caucasus of its ally Germany. During the TurkishTranscaucasian diplomatic negotiations in Batumi, the delegations of Georgia and Germany initially prepared the ground for the final disintegration of the already disconnected independent Transcaucasian republic. Finally, at noon on May 26, the Transcaucasian Seim decided to disband it. In the evening of the same day, the head of the Turkish delegation Khalil-bey presented an ultimatum, and four hours earlier Georgia proclaimed its independence. On May 28, the National Council of Muslims proclaimed independence at the request of tribal Turkey (the Caucasian Tatars appealed to the Turkish delegation with a request to facilitate their entry into Turkey, but the request was rejected ...). On May 30, the National (Central) Council of Armenians declared itself the supreme and sole authority in the Armenian provinces.